Non-linear effects in hopping conduction of single-crystal La₂CuO₄₊δ - Belevtsev, B.I.; Dalakova, N.V.; Panfilov, A.S. (Физика низких температур, 1998)
The unusual non-linear effects in hopping conduction of single-crystal La₂CuO₄₊δ with excess oxygen has been observed. The resistance is measured as a function of the applied voltage U (voltage controlled regime) in the temperature range 5 K≤T≤300 K and voltage range 10⁻³−25 V. At relatively high voltage (approximately at U>0.1 V) the conduction of sample investigated corresponds well to variable-range hopping (VRH). That is, in the range 0.1 V<U⩽1 V the conductivity does not depend on U (Ohmic behavior) and the temperature dependence of resistance R(T) follows closely Mott’s law of VRH [R∝exp(T₀/T)¹/⁴]. In the range of highest applied voltage the conduction has been non-Ohmic: the resistance decreases with increasing U. This non-linear effect is quite expected in the frame of VRH mechanism, since the applied electric field increases the hopping probability. A completely different and unusual conduction behavior is found, however, in the low voltage range (approximately below 0.1 V), where the influence of electric field and (or) electron heating effect on VRH ought to be neglected. Here we have observed strong increase in resistance at increasing U at T≤20 K, whereas at T>20 K the resistance decreases with increasing U. The magnetoresistance of the sample below 20 K has been positive at low voltage and negative at high voltage. The observed unusual non-Ohmic behavior at low voltage range is attributable to inhomogeneity of the sample, namely, to the enrichment of sample surface with oxygen during the course of the heat treatment of the sample in helium and air atmosphere before measurements. At low enough temperature (below ≈20 K) the surface layer with increased oxygen concentration is presumed to consist of disconnected superconducting regions in a poorly conducting (dielectric) matrix. This allows us to explain the observed unusual non-linear effects in the conduction of sample studied. The results obtained demonstrate that in some cases the measured transport properties of cuprate oxides cannot be attributed to the intrinsic bulk properties.
Remove selected